AMPHITRITE AS A SOURCE OF IDEAS FOR PARTY DRESS WITH BEADS EMBROIDERY - Alexandra, Salma Calista; Wiana, Winwin (Universitas Negeri Yogyakarta, 2025)
This study examines the creation of a party dress inspired by Amphitrite, a sea goddess from Greek mythology, with the potential to be a valuable source of ideas for making a party dress with beads and embroidery garniture. The main objective of this research is to create an aesthetically pleasing party dress with a cultural value that could elevate the elegance of the dress. The Double Diamond model method is used to conduct further studies. In the Discover stage, information on Amphitrite was gathered from various sources and synthesized into a mood board. During the Define stage, three design concepts were developed, with one selected for further refinement based on its alignment with Amphitrite's mythological persona. The development stage visualizes the chosen design, incorporating flowing fabrics to reflect ocean waves and intricate details. The Deliver stage focused on elevating the value of the dress, with the beading embroidery technique added to enhance its connection to ancient history within the dress. The final product is a figure-hugging party dress with a hidden tale of Amphitrite through the trident as a bedazzled garniture that adorned the front of the dress. Future research may explore other mythological figures or integrate advanced techniques to deepen the fashion narrative.